THE IMPORTANCE OF AUTHENTIC MATERIALS TO SUPPORT STUDENTS’ READING PROFICIENCY - Robi Soma (Global Expert: Jurnal Bahasa dan Sastra, 2018)
In teaching English as a foreign language, teachers frequently use authentic materials to teach their students in the classroom. Both in four language skills namely reading, listening, speaking, and writing and language components like grammar and vocabulary. In addition, these kinds of materials have greater influence to enhance students’ foreign language ability because they are introduced directly to the materials which use English as the introductory language.   This paper discusses what is meant by authentic text, kinds of authentic materials, why it is important to use this material, the strengths and weaknesses of using this material in teaching reading to EFL students in relation to the enhancement of students’ reading proficiency. Key words : authentic materials, reading proficiency, EFL students